Advancing knowledge through literature reviews: 'what', 'why', and 'how to contribute'. Issue 7 (11th June 2022) - Lim, Weng Marc; Kumar, Satish; Ali, Faizan
ABSTRACT: Literature review is part and parcel of scholarly research. Though many literature review guides are available, they remain limited because they do not adequately account for the different types of literature review. Noteworthily, literature reviews can manifest as part of conceptual or empirical studies, or as independent studies, in which the latter may be curated in various ways. Moreover, despite its importance and popularity, literature reviews, particularly as independent studies, continue to attract unfair criticism and remain scarce in service research. To address the aforementioned gaps, this article endeavors to provide an overview and guidelines for writing literature reviews. Specifically, this article explains (1) what a literature review is and is not, (2) why literature reviews are valuable, and (3) how to conduct a literature review, as well as (4) the areas of service research and (5) the innovative ways in which literature reviews can be curated in the future.